Insulin refusal in uncontrolled Type 2 Diabetes in Bangladesh: Barriers and the role of patient-centered education (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2026)
Background: Reasons for insulin refusal among uncontrolled type 2 diabetes (T2D) are well-documented, yet the effect of patient-centered education (PCE) remains insufficiently studied in Bangladesh.Objectives: This study aimed to identify reasons for insulin refusal and to evaluate the effectiveness of PCE on insulin acceptance.Method: This cross-sectional study included patients with uncontrolled T2D from the outpatient department of three hospitals in Bangladesh between April 2024 and September 2025. All initially refused insulin despite clinical indications. Reasons for refusal were identified via interviews. A subset of 113 patients received physician-delivered PCE, and acceptance rates were recorded. Logistic regression analyzed factors associated with continued refusal.Results: The study consisted of 202 patients (age: 48.4±11.5 years, mean ± SD, female: 134, 66.3%, mean HbA1c: 10.90±1.93%). The most common reasons for initial refusal were needle phobia (153, 75.7%), followed by absence of a caregiver for injections (47, 23.3%) and lack of knowledge of injection technique (45, 22.3%). Following PCE, 61.1% (69/113) of patients agreed to initiate insulin. We found higher odds for refusal among undergraduates (OR: 7.09; 95% CI 1.05-47.93, p=0.002) and rural residents (OR: 1.84; 95% CI 1.04-3.25, p=0.018), while male sex (OR: 0.36; 95% CI 0.17-0.78, p=0.002) and duration of DM